The restless wave : good times, just causes, great fights and other appreciations - McCain, John, 1936-2018; Salter, Mark (Simon & Schuster, 2018)
Summary: "A candid new political memoir from Senator John McCain--his most personal book in years--covering everything from 2008 up to the present."--Provided by publisher.